Agricultural dust explosions in 2011 - Ambrose, R. P. Kingsly (Kansas State University. Dept. of Grain Science and Industry, 2015)
There were 9 dust explosions reported in the U.S. in 2011 according to Kingsly Ambrose, Assistant Professor, Kansas State University. This compares to 11 in 2010 and a ten-year average of 9.8 explosions.
Keywords: Grain dust; Dust explosions